High-throughput screening for small molecule inhibitors of the type-I interferon signaling pathway - Elita Yuliantie; Xinchuan Dai; Dehua Yang; Peter J. Crack; Ming-Wei Wang (Elsevier, 2018)
Interferons (IFNs) are cytokines with fundamental roles in resistance to infections, cancer and other diseases. Type-I IFNs, interferon α (IFN-α) and interferon β (IFN-β), act through a shared receptor complex (IFNAR) comprised of IFNAR1 and IFNAR2 subunits. Binding of type-I IFN to IFNAR1 will robustly activate Janus activated kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway. Aberrant activation of the type-I IFN response results in a spectrum of disorders called interferonopathies. The purpose of this research is to develop an assay for high-throughput screening (HTS) of small molecule inhibitors of the type-I IFN signaling pathway. Inhibition of type-I IFN signaling can be beneficial in terms of therapeutic use and understanding the underlying mechanism of action. We report here a HTS campaign with the secreted embryonic alkaline phosphatase (SEAP) reporter gene assay against 32,000 compounds which yielded 25 confirmed hits. These compounds were subsequently characterized for their cytotoxicity, effects on STAT phosphorylation and activities in IFN regulatory factor (IRF) transcription. KEY WORDS: High-throughput screening, Interferon α receptor, Secreted embryonic alkaline phosphatase, JAK-STAT, IFN regulatory factor, Inhibitor